The Effectiveness of Fable-Based Picture Book in Teaching Reading Comprehension of Narrative Text to Junior High School - Pebriyani, Pebi; Surayya, Siti Ayu; Usuluddin, Usuluddin; Agustina, Yulia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to improve students’ reading comprehension skills in narrative text using a fable-based picture book. The participants of the study were seventh-grade students at MTs. Unwanul Falah NW Paok Lombok in the 2025-2026 academic year. Sample consisted of two classes divided into experimental and control groups. This study used a quasi-experimental method with non-equivalent control group design. Data were collected through pre-test and post-test. The results of the data analysis showed that the average post-test score of the experimental class reached 77.35, while the average post-test score of the control class was 68.82. The independent sample t-test analysis showed a significance value (2-tailed) of 0.036 0.05, indicating that Ho was rejected and Ha was accepted. Therefore, it can be concluded that fable-based picture book improved the reading comprehension skill of seventh-grade students at MTs. Unwanul Falah Nahdatul Wathan Paok Lombok.